Prevalence of anxiety and associated risk factors among maternal and child health hospital female attenders: a cross-sectional multicenter study - Song, Cheng; Tang, Jia; Shi, Zhixin; Tang, Shiru; Wang, Zirui; Zhang, Guanlin; Liu, Siyuan; Chen, Xu; Song, Yueping (Frontiers in Psychology, 2026)
Background/ObjectivesMaternal anxiety represents a substantial public health concern, particularly among women who are attending Maternal and Child Health (MCH) hospitals. This study investigated anxiety prevalence and risk factors among MCH hospital female attenders in Henan Province, a region demographically representative of national trends, during the peak winter medical demand of December 2024.MethodsA cross-sectional study using convenience sampling was implemented to recruit 745 maternal participants from 5 MCH hospitals (comprising three Grade A tertiary hospitals and two other hospitals) in Henan Province of China during December 2024. Maternal anxiety was assessed using the Generalized Anxiety Disorder 7-item scale (GAD-7). Knowledge regarding maternal and child healthcare and self-efficacy in accessing healthcare services were evaluated using the self-developed Maternal and Child Health Knowledge Scale (Cronbach’s α = 0.932) and the Self-Efficacy in Healthcare Access Scale (SEHAS) (Cronbach’s α = 0.964). Statistical analyses were performed using univariate and multivariate logistic regression models to determine the association between sociodemographic/clinical factors and anxiety symptoms.ResultsThe overall prevalence of anxiety was 30.5% (95% CI: 26.8–34.1%). Anxiety was significantly associated with hospital level, departmental affiliation, and participants’ knowledge regarding healthcare. Specifically, higher anxiety levels were found among females attending Grade A tertiary MCH hospitals versus other hospitals (Reference: Other hospital; Grade A tertiary hospital, AOR = 2.318, 95% CI = 1.580–3.402), and being in the Pediatric Department was a stronger risk factor than being in the Maternity Department (AOR = 0.501) or reproductive services (AOR = 0.584). Additionally, lower scores in maternal healthcare knowledge (AOR = 0.967, 95% CI = 0.940–0.995) and self-efficacy in healthcare access (AOR = 0.954, 95% CI = 0.913–0.997) were significantly correlated with increased anxiety symptoms.ConclusionOur findings highlight a critical need for the integration of mental health screening and tailored interventions within maternal healthcare frameworks. Enhancing maternal health literacy, improving accessibility to psychological support, and developing specific interventions based on healthcare settings and departments are crucial for addressing anxiety and improving maternal health outcomes.